2021
DOI: 10.3389/fimmu.2021.725244
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Pneumococcal and Haemophilus influenzae Natural Antibody Development in Papua New Guinean Children in the First Year of Life

Abstract: BackgroundDevelopment of vaccines to prevent disease and death from Streptococcus pneumoniae, and nontypeable Haemophilus influenzae (NTHi), the main pathogens that cause otitis media, pneumonia, meningitis and sepsis, are a global priority. Children living in low and lower-middle income settings are at the highest risk of contracting and dying from these diseases. Improved vaccines with broader coverage are required. Data on the natural development of antibodies to putative vaccine antigens, especially in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…We wish to identify if immunisation increases maternal and cord blood IgG antibodies to vaccine-type pneumococcal serotypes and to H. influenzae PD. This is significant as a recent study from Papua New Guinea suggested that antibodies to NTHi outer membrane proteins may not be transferred from mothers to their infants ( 72 ). We will also determine innate and systemic immune responses to pneumococci and H. influenzae in both mothers and their infants.…”
Section: Discussionmentioning
confidence: 99%
“…We wish to identify if immunisation increases maternal and cord blood IgG antibodies to vaccine-type pneumococcal serotypes and to H. influenzae PD. This is significant as a recent study from Papua New Guinea suggested that antibodies to NTHi outer membrane proteins may not be transferred from mothers to their infants ( 72 ). We will also determine innate and systemic immune responses to pneumococci and H. influenzae in both mothers and their infants.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, >80% cross-reactivity was demonstrated between rsPilA and ChimV4, with little cross-reactivity observed with/between other antigens (<10%). All antigens were conjugated to fluorescent carboxylated microspheres for measurement of serum IgG-specific titres ( Martinovich et al., 2021 ). Briefly, samples were diluted 1:200 in serum diluent (phosphate buffer saline, 2% bovine serum and 0.05% tween20).…”
Section: Methodsmentioning
confidence: 99%
“…Pure, stable and endotoxin free recombinant PD was produced by the Protein Expression Facility (The University of Queensland) according to optimised protocols and adapted from methods used previously ( 33 ). H. influenzae antigens OMP26, rsPilA and ChimV4 were prepared as described previously ( 21 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sera were assessed for specific IgG antibodies against S. pneumoniae antigens PspA1, PspA2, CbpA, Ply, and H. influenzae antigens PD, OMP26, rsPilA and ChimV4 using multiplex bead-based immunoassays that have been described previously ( 21 ). The final assays consisted of a 5-plex immunoassay containing PspA1, PD, ScpA ( Streptococcus pyogenes antigen, data not shown here), OMP26 and rsPilA, and a 4-plex immunoassay containing PspA2, CbpA, Ply and ChimV4.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation